Implementation of the Rantang Kasih Program in Ensuring the Welfare of Poor Elderly Alone - Mohammad Yusuf Efendi; Putri Robiatul Adawiyah (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The elderly are a vulnerable group who cannot carry out productive activities in their lives. Decreased physical condition, loss of social influence and function, and increased dependence on others, encourage the Elderly group as a target in social protection programs. Social protection serves as a guardian of the welfare of the elderly from poverty and hunger. The Rantang Kasih Program of Banyuwangi Regency is a food program for the elderly. This research aims to explain how the implementation of the Rantang Kasih policy/program in Pengatigan Village, Rogojampi District, Banyuwangi Regency. This research uses a qualitative method with a descriptive approach. It was carried out for one month (May) by involving village officials and program target communities as informants, and literature study activities. This research is measured by Merilee S. Grindle's policy implementation theory. The results showed that the implementation of the Rantang Kasih program in Pengatigan Village in the year used funding sources from the Pengatigan Village budget (APBDes). The amount/ration of rantang food is once a day, the food is made from stalls closest to the homes of the elderly program recipients, and delivered by village officials and / or stall managers. The implementation of the Rantang Kasih program in Pengatigan Village has been in accordance with the guidelines regulated through the Regent Regulation.